Analisis pendapatan pedagang kaki lima di Kota Jambi (studi kasus pedagang kaki lima di Jalan Jenderal Basuki Rahmat sampai H. Agus Salim Kecamatan Kota Baru) - Panggno Septiawan; Rahma Nurjanah; Candra Mustika (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2019)
This study aims: 1) To find out and analyze the socio-economic characteristics of street vendors on Jalan Basuki Rahmat until General H. Agus Salim; 2) To find out and analyze what factors influence the income of street vendors on Jalan Basuki Rahmat until Jenderal H. Agus Salim by using multiple linear regression analysis tools. Based on the analysis of the characteristics of street vendors who are respondents according to the average age of 33 years, the highest sex is male, the most marital status is married, the number of family dependents is 3 dependents, according to the highest level of education, namely high school, the length of hours work that is 8 hours working time in a day, selling as a main job, average fixed capital of Rp. 2,212,000, operating capital with an average of Rp. 250,000 per day and for an average income of Rp. 3,376,000 per month. Based on the regression results indicate that the variables of capital, age, and working hours have a significant effect on the income of street vendors. Keywords: Income, Capital, Age, Working Hours, Education Level.